Tinjauan Maqāșid Al-Sharī’ah Terhadap Dispensasi Nikah - Lauhul Mahfudz (ISTIDLAL, 2022)
The age limit for marriage contained in the Marriage Law Number 1 of 1974 which is also mentioned in the Compilation of Islamic Law is the result of ijtihad, although in classical literature it is not found. The age limit itself is an attempt to avoid damage. On the other hand, the law provides leeway for prospective brides who are still under the age limit to request dispensation through the Religious Courts. In this regard, of course, judges are required to decide wisely without violating the Shari'a. This research is focused on Maqāșid al-Sharī'ah's review of marriage dispensation. With the emphasis of this study, this study uses the Maqāșid al-Sharī'ah approach. Meanwhile, according to the emphasis of the study, this research is classified as a normative rule research. Meanwhile, if observed according to the data collection operations studied, it is included in the category of library research (library study). Considering that this research belongs to the category of normative rule research in the form of library research, the research framework is classified as qualitative using a flow of thought and an inductive-deductive work pattern. The results of the study indicate that the dispensation in its implementation is divided into three, first; prospective partner who is not old enough and has never had sex, second; the potential partner is under the legal age, has had sex, but is not pregnant. both according to the perspective of Maqāșid al-Sharī'ah are not allowed to give permission for dispensation, and the third, namely the prospective partner who has not reached the age, has had sex and is pregnant, according to the perspective of Maqāșid al-Sharī'ah it is better to give permission for kawi dispensation.